EFESIENSI METODE MUROJA’AH DALAM MEMPERKUAT HAFALAN AL-QUR’AN SANTRI PPTQ MASJID AGUNG SURAKARTA - Luthfi Badrus Tsani (MAMBA'UL 'ULUM, 2022)
This study aims to determine the efficiency of the Muroja'ah method in memorizing the Qur'an of students. The subject of this research is the PPTQ of the Great Mosque of Surakarta. This research is a qualitativeresearch with data collection methods through observation, interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation and data verification. The results found in this study indicate that the muroja'ah method implemented at the PPTQ of the Great Mosque of Surakarta is the new memorization Muroja'ah independently, then deposited to the ustadz, muroja'ah old memorization to a friend, muroja'ah memorizing lama (sima'an) in front of the santri and asatidh, murojaah memorizing in prayer times, repeating (muroja'ah) with aids, repeat memorization by writing in a book or sheet of paper, and final examination in repeating memorization. Then the murojaah method is based on the achievements of new and old memorization every day.